Multicenter randomized trial comparing diagnostic sensitivity and cellular abundance with aggressive versus standard biliary brushing for bile duct stenosis without mass syndrome - Karsenti, David; Privat, Jocelyn; Charissoux, Aurélie; Perrot, Bastien; Leblanc, Sarah; Chaput, Ulriikka; Boytchev, Isabelle; Levy, Jonathan; Schaefer, Marion; Bourgaux, Jean-François; Valats, Jean-Christophe; Coron, Emmanuel; Moreno-Garcia, Maira; Vanbiervliet, Geoffroy; Rahmi, Gabriel; Robles, Enrique Perez-Cuadrado; Wallenhorst, Timothée (Endoscopy, 2023)
Background The diagnosis of cholangiocarcinoma in patients with a biliary stricture without mass syndrome can be obtained by biliary brushing with a sensitivity of ~50 %. We performed a multicenter randomized crossover trial comparing the aggressive Infinity brush with the standard RX Cytology Brush. The aims were to compare sensitivity for cholangiocarcinoma diagnosis and cellularity obtained.Methods Biliary brushing was performed consecutively with each brush, in a randomized order. Cytological material was studied with blinding to the brush type used and order. The primary end point was sensitivity for cholangiocarcinoma diagnosis; the secondary end point was the abundance of cellularity obtained with each brush, with cellularity quantified in order to determine if one brush strongly outperformed the other.Results 51 patients were included. Final diagnoses were cholangiocarcinoma (n = 43; 84 %), benign (n = 7; 14 %), and indeterminate (n = 1; 2 %). Sensitivity for cholangiocarcinoma was 79 % (34 /43) for the Infinity brush versus 67 % (29/43) for the RX Cytology Brush (P = 0.10). Cellularity was rich in 31/51 cases (61 %) with the Infinity brush and in 10/51 cases (20 %) with the RX Cytology Brush (P < 0.001). In terms of quantification of cellularity, the Infinity brush strongly outperformed the RX Cytology Brush in 28/51 cases (55 %), while the RX Cytology Brush strongly outperformed the Infinity brush in 4/51 cases (8 %; P < 0.001).Conclusions This randomized crossover trial showed that the Infinity brush is not significantly more effective than the RX Cytology Brush for biliary stenosis without mass syndrome in terms of sensitivity for cholangiocarcinoma diagnosis, but does offer a significantly higher abundance of cellularity.